A new efficient method for determining the collapse margin ratio using parallel computing. (February 2015) - Hardyniec, Andrew; Charney, Finley
Highlights: We present a new parallel computing method for finding the collapse margin ratio. The method is faster than an incremental dynamic analyses using serial computing. The new method is more efficient than similar parallel computing methods. The method is demonstrated using two four-story example frames. We provide recommendations for overcoming convergence issues during analyses. Abstract: The collapse margin ratio (CMR) is an important value in the FEMA P-695 process. However, determination of the CMR is computationally intensive and the duration for running a full incremental dynamic analysis (IDA) using serial computing to calculate the CMR can be prohibitive. In response to this restriction, a new efficient search method was created for finding the collapse margin ratio for a structural model using parallel computing. The proposed method does not require a full IDA and provides a significant decrease in the time required to determine the CMR compared to running a full IDA using serial computing. The new method is compared against similar methods for finding the CMR in parallel using both a four-story buckling restrained braced frame and a four-story steel moment resisting frame. Recommendations for overcoming convergence issues are discussed to aid in the application of the search method.